Pedofunctions applied to the least limiting water range to estimate soil water content at specific potentials - Tavanti, Renan F.R. [UNESP]; Freddi, Onã da S.; Tavanti, Tauan R. [UNESP]; Rigotti, Adriel; Magalhães, Wellington de A. (FapUNIFESP (SciELO), 2019)
The least limiting water range (LLWR) is a soil physical quality indicator that receives much attention. It has been criticized and put to the test regarding mathematical models that compose it since they describe the behavior of soil physical attributes in a simplified way. This study aimed to assess the efficiency of some pedofunctions proposed in the literature and artificial neural networks on the accuracy in predicting soil water retention at potentials equivalent to field capacity (θFC) and permanent wilting point (θPWP). In other words, to apply the best models to LLWR of two soil types (Oxisol and Ultisol) and verify changes in their structure. The results indicated that pedofunctions using sand, silt, clay, bulk density, and soil organic matter contents are more efficient in estimating θFC and θPWP. However, the use of multiple linear regression models to predict θFC values below 0.20 m3 m-3 may present a slight tendency to overestimate it, which is not observed in the neural networks. As in R2, equations from neural networks were more efficient in estimating θFC and θPWP. Pedofunctions used to calculate LLWR differ in the establishment of the critical soil bulk density, exposing the limitations of the model.
Keywords: Artificial neural networks; Available water; Pedotransfer functions; Soil physical quality indicator; Soil physics